Phenomenal Impacts of Climate Change and Emigration on Agricultural Production in Nigeria - Osuji, E. E.; Tim-Ashama, A. C.; Obi, J. N.; Eze, E. U.; Essien, U. A.; Orji, J. E.; Ibrahim-Olesin, S.; Chinaka, I. C.; Inyang, P.; Njoku, U. G. (Current Topics in Agricultural Sciences Vol. 6, 2022)
Contributions of agriculture to gross domestic product in Nigeria had dropped consequent upon several factors, most especially; climate change and emigration. Thus, the study reviewed the phenomenal impacts of climate change and emigration on agricultural production in Nigeria. Objectives of the study were to assess the negative and positive impacts of climate change on agricultural production and the associated effects of emigration in Nigeria. Negative impact of climate change is seen on reduced food production, poverty, high prices of commodities, destruction of arable lands, aquatics, etc. While it’s positive sides includes activation and aiding of soil microbial organisms, thus enhancing soil aeration, soil structure and texture. Others are increased in plant growth and photosynthetic aiding of crops. Emigration poses doubled impacts as it diminishes agricultural labour force in the migrant location, and increases the labour force in the destination. The study recommends increased awareness on impacts of climate change and provision of rural infrastructures to reduce rural-urban drift.